2016
DOI: 10.1590/1413-785220162403153479
|View full text |Cite
|
Sign up to set email alerts
|

Knee Synergism During Gait Remain Altered One Year After Acl Reconstruction

Abstract: Objective: To compare the activation of the vastus lateralis (VL) and biceps femoris (BF) muscles during gait, as well VL/BF muscular co-contraction (MCC) between healthy (CG) and anterior cruciate ligament reconstructed (ACL-R) subjects.Methods: Nineteen subjects, ten controls and nine ACL-R patients had a VL and BF electromyogram (EMG) captured to calculate the MCC ratio. A Principal Component (PC) Analysis was applied to reduce the dimensionality effect of each of the MCC, VL and BF curves for both healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Arthrogenic muscle inhibition also shows in the daily movement. Several studies' results suggested that there is an increase in hamstring activation (Knoll et al, 2004;Mantashloo et al, 2020) and a decrease in quadriceps femoris activation (Leporace et al, 2016) among ACLR patients during walking. The altered biomechanics in movement will significantly affect the mechanical environment of the knee joint, which may increase the risk of knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Arthrogenic muscle inhibition also shows in the daily movement. Several studies' results suggested that there is an increase in hamstring activation (Knoll et al, 2004;Mantashloo et al, 2020) and a decrease in quadriceps femoris activation (Leporace et al, 2016) among ACLR patients during walking. The altered biomechanics in movement will significantly affect the mechanical environment of the knee joint, which may increase the risk of knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%